If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -1(3x + 30) = 12 Reorder the terms: 9x + -1(30 + 3x) = 12 9x + (30 * -1 + 3x * -1) = 12 9x + (-30 + -3x) = 12 Reorder the terms: -30 + 9x + -3x = 12 Combine like terms: 9x + -3x = 6x -30 + 6x = 12 Solving -30 + 6x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + 6x = 12 + 30 Combine like terms: -30 + 30 = 0 0 + 6x = 12 + 30 6x = 12 + 30 Combine like terms: 12 + 30 = 42 6x = 42 Divide each side by '6'. x = 7 Simplifying x = 7
| 23+2y-9=11y-14-5Y | | 105n=-140n | | .17(1.2)= | | 4(a-2)=3a | | 22-7x=111 | | -3(t-1)+6t=5t-1 | | 3(x-4)=8x-5-5x | | 7x+2-x=5+5x-2 | | -6x^2-10=0 | | 6x+4=4(x+3) | | -3x+5+4x=-5+22 | | 10=-6x^2 | | 6-4y=11-8y+4y | | 4x^7+6x^2=0 | | 20x-6=50x+12 | | 36-8m=8m-7m | | y+2.5=-8.5-7.6 | | -3x+21=4x | | 1320=-2x+1200 | | 1320=6x | | 5d^2-45=0 | | x^2-12x-12=0 | | 5u+4.6=10.6 | | -5y-1(5y-9)=1+2(8-y) | | 6(x+9)+2=-8(x-7)-9 | | 5(5y+4)-17=6(3y-3)-7 | | 4(3x+21)=24 | | 5x+1=4(x+5)+9 | | 8(x-11)-6=20x-190 | | 20+-25= | | -2(9n+4)=22-7n | | h^2-3h+c=0 |